Antara Sunnah dan Adab: Memahami Hadist Kencing Berdiri - Megawati Kusuma Dewi, Trisia; Syukri Pulungan, Muhammad (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
Religion is a guide to life for every believer. In Islam, guidance comes from the Book of Allah which is the main source and the hadith/sunnah is the second source. In the hadith, many behaviors are stated in detail in several hadith texts. One of them is about urinating, whether done sitting or standing, which can be found in the Tis`ah pole which is narrated by various hadith narrators. The main hadith books summarized in the Tis`ah pole contain a collection of ḥadith of Rasulullah S.A.W, both in the form of words, in the form of actions and approvals of Rasulullah S.A.W which provide an overview of creed, shari'ah, muamalah and morals. In several wiraya it is stated that Rasulullah S.A.W urinated while sitting, but there are also hadiths which state that Rasulullah S.A.W also urinated while standing. On the basis of the quality and continuity of the hadith sanads, it can be said that all the narrators of both hadiths are tsiqat and the sanads are continuous from the first narrator to the last narrator (mukharijj hadith). In general, it seems that these two hadiths contradict each other, which is then known as the mukhtalaf hadith.